A global analysis of portion size recommendations in food-based dietary guidelines - Salesse, Fanny; Eldridge, Alison L.; Mak, Tsz Ning; Gibney, Eileen R. (Frontiers in Nutrition, 2024)
Objective: Since large food portion sizes (PS) lead to overconsumption, our objective was to review PS recommendations for commonly consumed food groups reported in Food-Based Dietary Guidelines (FBDGs) globally and to assess variation in PS across countries and regions. Methods: Consumer-oriented FBDGs from the Food and Agriculture Organisation (FAO) online repository were used to evaluate dietary recommendations, PS and number of portions for common food groups. Guidelines were classified for each group as qualitative, quantitative, or missing. A standardized approach was applied to convert PS recommendations given as household measures, cup equivalents, pieces and other measures into grams for cross comparison. Variation of recommended PS of common food groups within and across regions was examined. Results: Among 96 FBDGs, variations were found both across and within regions. At a regional level, the highest regional median PS recommendations were seen in Europe for Meat, Fish and Pulses, in the Near East for Dairy Products, and in Africa for most grain-based foods. Recommendations for Fruits and Vegetables showed the highest consistency across FBDGs worldwide, whereas guidance on Meat, fish & eggs and Cooked cereals/grains showed discrepancies in the classification of foods into categories, as well as in the number of portions per day. Discussion: While some variation in PS recommendations across countries can be expected due to cultural and regional dietary practices, inconsistent definitions to refer to a portion and varied derivation methods may further produce discrepancies. Harmonizing development methods for FBDG could help establish more consistent reference portion sizes and therefore provide clearer guidance to consumers.